Prevalence and Risk Factors of Bronchial Asthma in Children - Kobilzhonova Sh.R; Mirrakhimova M.Kh; Sadullaeva Kh.A (Zien Journals, 2022)
Identify clinical and laboratory features of the course of bronchial asthma in children living under the influence of adverse environmental factors.
Keywords: epidemiological; clinical and laboratory; functional and statistical research methods; course